Do E‐verify mandates improve labor market outcomes of low‐skilled native and legal immigrant workers?. (April 2015) - Bohn, Sarah; Lofstrom, Magnus; Raphael, Steven
<x xml:space="preserve">Abstract</x> We examine the impact of the 2007 Legal Arizona Workers Act (LAWA) on employment outcomes of low‐skilled legal workers. We use the synthetic control method to select a group of states against which the labor market trends of Arizona can be compared. Our results suggest that contrary to its intent, LAWA does not appear to have improved labor market outcomes of legal low‐skilled workers who compete with unauthorized immigrants, the target of the legislation. In fact, we find some evidence of diminished employment and increased unemployment among legal low‐skilled workers in Arizona. These findings are concentrated on the largest demographic group of workers—non‐Hispanic white men. While they are less likely to find employment, those who do have on average higher earnings as a result of LAWA. The pattern of results points to both labor supply and labor demand contractions due to LAWA, with labor supply dominating in terms of magnitude.